Transparency and dealer behavior: The case of MiFID II and the bund market - Konrad Lucke (Leibniz Institute for Financial Research SAFE, 2026)
We study how the introduction of pre- and post-trade transparency requirements affected dealer behavior and market liquidity in the German sovereign bonds market. Using regulatory data on bond transactions collected under EU's Markets in Financial Instruments Regulation (MiFIR) and limit order book data from the Mercato Telematico dei Titoli di Stato (MTS) interdealer platform, we show that the reform had a positive effect on market liquidity, especially in the previously opaque market segments. However, it also led to a significant deterioration in market conditions in the MTS central limit order book. After dealers were required to publicly disclose quotes and trades to the rest of the market, bid-ask spreads widened and price discovery weakened. The evidence indicates that transparency reduced dealers' willingness to post competitive quotes in the limit order book, undermining the informational efficiency of this benchmark market. These findings highlight that greater transparency can discourage liquidity provision and weaken the mechanisms of price formation in interdealer markets.
Keywords: G14; G18; D47; 330; Sovereign bonds; market microstructure; market liquidity